2016
DOI: 10.3386/w22628
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Impact Dynamics of a Rural Business Development Program in Nicaragua

Abstract: through the BASIS Assets and Market Access CRSP. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
0
9
0
2
Order By: Relevance
“…Another example of a non-integrated VCD project directed at the farmer is the Rural Business Development program, evaluated by Carter et al (2016), in which farmers receive technical and marketing assistance and are financially supported in acquiring the necessary equipment and materials to implement their individual business plans. Carter et al find no effects of this project on consumption expenditures.…”
Section: Effectiveness Of Public Initiatives For Value Chain Developmentmentioning
confidence: 99%
“…Another example of a non-integrated VCD project directed at the farmer is the Rural Business Development program, evaluated by Carter et al (2016), in which farmers receive technical and marketing assistance and are financially supported in acquiring the necessary equipment and materials to implement their individual business plans. Carter et al find no effects of this project on consumption expenditures.…”
Section: Effectiveness Of Public Initiatives For Value Chain Developmentmentioning
confidence: 99%
“…Other studies of smallholder matching funds programs have found positive effects on the adoption of technologies or production practices (Ton et al 2015;Maffioli et al 2013) as well as production, yield, and revenue (Ton et al 2015;Carter, Tjernström and Toledo 2016;Mullally and Maffioli 2016). Our results support the positive findings of the existing literature for the indicators just described.…”
Section: Resultsmentioning
confidence: 99%
“…al., 2018;Furmankiewicz et. al., 2016;Carter et. al., 2019) and agricultural programs such as electrification (Ding et.…”
Section: Introductionmentioning
confidence: 99%